PENGARUH KEPEMIMPINAN, MOTIVASI, DAN KOMPETENSI TERHADAP KINERJA MELALUI KEPUASAN PADA GURU SMK MUHAMMADIYAH BULAKAMBA BREBES - Aly Murtadlo; Mr. Tabrani (Multiplier: Jurnal Magister Manajemen, 2016)
The purpose of this research is 1) for described leadership, motivation, competence, satisfaction and performance of teachers 2) to analyze the influence of leadership, motivation, and competence to satisfaction teachers 3) to analyze the influence of leadership, motivation, and competence of the performance of teachers 4) to analyze the influence of satisfaction with performance of teachers 5) to analyze the influence of leadership, motivation, and competence of the performance of through satisfaction teachers. Respondents in this research as many as 38 people. These respondents teachers are smk muhammadiyah bulakamba brebes. This research using structural equation modeling (shem) run through amos 19 as a means of the analysis. The results of the analysis data prove that leadership, motivation, and competence influential in significant impact on satisfaction teachers as evidenced of the value of the regression coefficient terstandar (beta) as much as 0,56, motivation work against satisfaction work teachers have value of 0.24 and competence to satisfaction work teachers get value 0.19. Leadership, motivation, and competence influential in significant impact on performance of teachers who evidenced of the value of the regression coefficient terstandar (beta) leadership of the performance of teachers get value 0.12, motivation work of the performance of teachers get value by 0.39 and competence of the performance of teachers have value of 0,46. Satisfaction influential significantly of the performance of teachers. This is evidenced from the p-value very small (<0,001). Leadership, motivation, and competence influential significantly on performance through satisfaction teachers as evidenced from the p-value sanggat small ( <0,00 ). Keywords: style leadership, motivation, competence, satisfaction, performance